Unlocking SME Potential: How Digital and Organizational Readiness Influence Attitudes Toward Social Media Live Streaming - Yossie Rossanty; Ramadhan Harahap; Rani Ramadhani Nasution (Penerbit Jurnal Indonesia, 2024)
This study investigates the impact of digital and organizational readiness on SMEs' attitudes toward social media live streaming. Using a quantitative research design, data will be collected through a cross-sectional survey of SME business owners and managers, with a minimum sample size of 200 respondents. The key constructs explored include digital readiness, organizational readiness, and attitudes toward live streaming. Digital readiness is assessed through factors such as digital infrastructure, employee skills, and technological updates, while organizational readiness is measured by company culture, management commitment, and resource availability. Attitudes toward live streaming are evaluated based on beliefs in its strategic value and potential benefits for business growth. Data analysis will be conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships between these constructs and to test the study's hypotheses. It is anticipated that the findings will confirm that both digital and organizational readiness significantly influence SMEs' attitudes toward live streaming, facilitating its effective adoption and utilization. This research provides critical insights into how SMEs can strategically navigate the challenges and opportunities presented by social media live streaming, ultimately enhancing their business performance and customer engagement.